2022
DOI: 10.3390/educsci12010034
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mathematics to Non-Mathematics Majors through Problem Solving and New Technologies

Abstract: The role of mathematics in several scientific disciplines is undisputed; work and everyday life take great advantage of its application. Nevertheless, students often tend to not particularly like it and to consider it of little interest. It is also believed that only people with a certain attitude are capable of mastering the subject. In consideration of this, we aimed to help science students develop mathematical competences by designing a course specifically oriented to applications and problem solving. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…This result could already be shown by a metaanalysis [70], which found that "technology-assisted, internet-based, and computerassisted instruction or learning were related to positive belief appraisals" [70]. Marchisio et al [71] were also able to show that digitally assisted alternative learning methods positively affect beliefs of university students. In another study, it was found that offering "alternative experiences as learners of mathematics" ( [69], p. 28) can cause a belief change.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This result could already be shown by a metaanalysis [70], which found that "technology-assisted, internet-based, and computerassisted instruction or learning were related to positive belief appraisals" [70]. Marchisio et al [71] were also able to show that digitally assisted alternative learning methods positively affect beliefs of university students. In another study, it was found that offering "alternative experiences as learners of mathematics" ( [69], p. 28) can cause a belief change.…”
mentioning
confidence: 82%
“…Indeed, previous research has already revealed individual elements that seem to have an impact on changes in prospective teachers' beliefs. For example, alternative learning methods [69,71], teaching experiments that combine prospective teachers' theoretical and practical knowledge [51,76], as well as subsequent self-reflection [51], appear to have an impact on changing prospective teachers' beliefs. However, previous research has considered the impact on beliefs for each of these elements separately.…”
mentioning
confidence: 99%
“…Сравнительный анализ смешанного, дистанционного, электронного и виртуального обучения на примере студентов STI College Global City, Филиппины, содержится в работе [3], а в материалах [4] авторы из Политехнического института Порту, Португалия, описали возможности LMS Moodle в качестве инструмента онлайн-оценки для ряда учебных программ по математике. В совсем недавней обзорной работе [5] коллектив из Туринского университета, Италия, представил цифровую среду обучения, адаптированную под курс математики и биостатистики для будущих биотехнологов.…”
Section: методы исследования обзор публикаций по использованию Lms Mo...unclassified
“…In this context, it can be said in the discussion section of the research that the results of the research with this value will benefit the field literature. Marchisio, Remogna, Roman, and Sacchet (2022), in studies in mathematical science students and a lesson on problem solving by designing for particular applications, intended to assist learners to develop proficiency in research and as a result encouraging interaction between them, so that they become active users of the content to be adapted according to the personal requirements of learning and, at the same time, students problem-solving approach and the usefulness of the software achieves the results it is observed that the importance of the role that is high. This value, when combined with the results of the research, research problem-solving activities using technologies in application is given and up to 3 hours and by taking the time to applications of mathematics, and problem-solving skills potentiated the development of students, it is seen that results have been achieved.…”
Section: Reasoning and Technology Status Of The Participant Groups Pa...mentioning
confidence: 99%